A Consistent Power Management System Design for Solar and Wind Energy-Based Residential Applications - Esen, M.; Bayrak, Gökay; Cakmak, O.; Celikdemir, S.; Ozdemir, M. (Institute of Electrical and Electronics Engineers Inc., 2019)
The solar and wind energy-based systems are directly dependent on the weather conditions for power generating. Thus a reliable system that is not affected by environmental conditions is required for residential applications. This study presents designing a consistent power management system (PMS) for solar and wind energy-based residential applications to overcome this problem. The proposed PMS controls a hybrid power generator (HPG) system consisting of a photovoltaic (PV) array and a wind turbine to supply consistent energy to the residential loads without any energy interruption in real-time. The designed PMS checks the demand side power and provides the PV array power to the HPG system in the condition of sufficient solar energy. Unless the PV array does not supply the desired power, the demand side power is supplied by fed by a permanent magnet synchronous generator (PMSG)-based wind turbine and a battery. The required energy is supplied from the grid, in case, the power supplied by the wind turbine and the PV array does not meet the demand. The developed PMS measures the PV panel voltage, battery voltage, and inverter's output voltage in real time and controls the relay circuits by evaluating these electrical parameters. The experimental results obtained from the developed HPG system verify that the proposed PMS is reliable for residential applications, easily implemented, practical, and presents a low-cost solution to the subject. © 2019 IEEE.
1st IEEE Global Power, Energy and Communication Conference, GPECOM 2019 -- 12 June 2019 through 15 June 2019 -- -- 150174
Keywords: demand-side management; real-time power management; solar energy; wind energy